Investigation of Accuracy and Clinical Value of 3D Printed and Virtual Reality Models of Congenital Heart Disease - Lee, Shen-yuan (Curtin University, 2024)
This thesis investigates the accuracy of multiple data sets, such as patient cardiac CT images, 3D segmented data, and 3D printed heart models. Additionally, by interviewing and surveying medical professionals, examine the practical usefulness of 3D printed models and virtual reality in pre-surgical planning of congenital heart disease, medical education, and patient communication. This research study demonstrated the high accuracy of 3D printed models and clinical value of virtual reality in pre-surgical planning.